Tooth polishing agent with antibacterial effect and preparation method thereof

By using modified nano zinc oxide and modified nano hydroxyapatite in dental polish, combined with gluconic acid lactone, the problem of insufficient antibacterial function of tooth polishing agent is solved, and the correct Effective antibacterial and remineralization of teeth provide long-term oral health protection.

CN119280082AActive Publication Date: 2025-01-10GUANGZHOU RUOHONG HEALTH TECH CO LTD

Patent Information

Application Number
CN202411499184.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

While cleaning and whitening teeth, existing dental polishes lack effective antibacterial function, which cannot effectively prevent oral bacterial growth and dental diseases, and insufficient protection of enamel.

Method used

Using modified nano zinc oxide and modified nano hydroxyapatite, the surface coupling of tetraphenyl porphyrin and sodium fluoride is modified to form nanoparticles with high antibacterial activity, and combining gluconic acid lactone to form rod-shaped nanomicrometers Capsules, which provide continuous antibacterial and remineralization, enhance tooth strength.

Benefits of technology

It significantly improves the antibacterial effect of tooth polishing agents, forms a dense protective layer, blocks bacterial contact, reduces the production of harmful bacteria, promotes enamel remineralization, enhances tooth strength, and provides long-term oral health protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280082A_ABST
    Figure CN119280082A_ABST
Patent Text Reader

Abstract

The invention relates to the field of dental care, in particular to a tooth polishing agent with an antibacterial effect and a preparation method thereof, and the tooth polishing agent is prepared from the following raw materials: silicon dioxide, sodium carboxymethyl cellulose, xanthan gum, propylene glycol, cocamidopropyl betaine, glycerol, modified nano-zinc oxide, modified nano-hydroxyapatite, glucolactone, stevioside and sodium benzoate. The modified nano-zinc oxide, the modified nano-hydroxyapatite and the glucolactone play a role through a synergistic effect, the modified nano-hydroxyapatite is used as a carrier to adsorb chemical substances such as the modified nano-zinc oxide and the like to form rod-shaped nano microcapsules, and a compact and uniform protective layer is formed on the tooth surface through a nano-size effect; the glucolactone promotes slow release of the rod-shaped nano microcapsules, and the glucolactone, the rod-shaped nano microcapsules and the glucolactone form a dynamic balance system, so that the antibacterial and remineralization effects are continuously exerted, the tooth structure is strengthened, the pH value is adjusted, the oral environment is maintained, and comprehensive and long-acting protection is provided for oral health.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of dental care, in particular to a tooth polishing agent with antibacterial effect and a preparation method thereof. Background Art

[0002] Tooth polish is a product specially used for dental care. It is mainly used to clean and polish the tooth surface. It is usually used for professional teeth cleaning in dental clinics. Its main purpose is to remove stains, plaque and slight discoloration on the tooth surface, making the tooth surface smoother and more shiny. The initial tooth polishing materials were mainly powders such as calcium carbonate and quartz powder, but these materials have limited effects and are prone to damage to tooth enamel. Subsequently, finer abrasive materials such as aluminum oxide and silicon dioxide were introduced. These materials improve the polishing effect and reduce potential damage to teeth. However, these traditional tooth polishes mainly remove stains and plaque by physical means, and only focus on the cleaning and whitening effects of the product on teeth. With the continuous advancement of technology, people's demand for oral health is also increasing. Antibacterial tooth polishes show unique advantages. In addition to the traditional cleaning and polishing effects, antibacterial tooth polishes can effectively inhibit the growth of oral bacteria and provide more comprehensive protection for oral health. Antibacterial ingredients can form a protective film on the surface of teeth and continue to play an antibacterial role for a long time after polishing. At the same time, by inhibiting the growth of harmful bacteria, the risk of oral diseases such as tooth decay and gingivitis is reduced. It can also improve breath and help keep breath fresh by reducing bacteria that cause bad breath. In addition, for people with sensitive or easily inflamed oral cavity, antibacterial tooth polishes can also provide gentler protection. Therefore, it is of great significance to develop a safe and effective antibacterial tooth polish.

[0003] (1) Technical issues to be solved

[0004] The purpose of the present invention is to provide a tooth polishing agent with antibacterial effect and a preparation method thereof, which optimizes the material formula of the tooth polishing agent and combines modern nanotechnology to effectively improve the antibacterial effect of the tooth polishing agent, and provide a more lasting and effective antibacterial environment for the oral cavity. While ensuring the polishing effect, it also further strengthens the tooth structure by repairing tiny defects in the enamel, enhances tooth strength, effectively prevents oral diseases, and provides long-term protection for oral health.

[0005] (2) Technical solution

[0006] To achieve the above object, on the one hand, the present invention provides a tooth polishing agent with antibacterial effect, comprising the following raw materials in parts by weight: 8-12 parts of silicon dioxide, 2-4 parts of sodium carboxymethyl cellulose, 1-2 parts of xanthan gum, 1-2 parts of propylene glycol, 2-4 parts of cocamidopropyl betaine, 4-6 parts of glycerol, 0.5-1 part of modified nano-hydroxyapatite, 1-2 parts of gluconolactone, 1-2 parts of steviol glycosides, and 2-4 parts of sodium benzoate;

[0007] The tooth polishing agent with antibacterial effect also includes:

[0008] Modified nano zinc oxide;

[0009] The modified nano zinc oxide and silicon dioxide are in a weight ratio of 1:(8-12);

[0010] The modified nano zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano zinc oxide is 40-60nm, and the specific surface area is 120-150m 2 / g.

[0011] Furthermore, the preparation method of the modified nano zinc oxide comprises:

[0012] S11. Dissolve zinc acetate in purified water under stirring, stir for 0.5 to 1 h, then slowly add 0.1 mol / L sodium hydroxide solution, raise the temperature to 55 to 65 ° C, continue stirring and react for 4 to 6 h to obtain a first mixed solution;

[0013] S12. The first mixed solution was subjected to high-speed centrifugation at a speed of 6000 to 8000 rpm for 10 to 15 min, and the separated solid was washed three times with purified water and then vacuum dried at a drying temperature of 50 to 60 ° C. After drying for 12 to 14 h, zinc oxide was obtained and ground into powder for standby use;

[0014] S13. Dispersing zinc oxide in anhydrous ethanol under nitrogen protection and subjecting to ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz, subjecting the zinc oxide to ultrasonic treatment at room temperature for 0.5 to 1 h, slowly adding 3-aminopropyltriethoxysilane and subjecting the mixture to reflux at a reflux temperature of 75 to 80 ° C., and subjecting the mixture to reflux for 6 to 8 h to obtain a second mixed solution;

[0015] S14. The second mixed solution was subjected to high-speed centrifugation at a speed of 8000 to 10000 rpm for 15 to 20 min. The separated solid was washed three times with anhydrous ethanol and then vacuum dried at a drying temperature of 45 to 55 ° C. After drying for 8 to 12 h, the nano zinc oxide intermediate was ground into a powder for standby use;

[0016] S15. Dissolve tetraphenylporphyrin in N,N-dimethylformamide under stirring, slowly add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide after stirring for 1 to 2 hours, raise the temperature to 45 to 60° C., continue stirring for 4 to 6 hours to obtain a third mixed solution;

[0017] S16. Disperse the nano zinc oxide intermediate in N,N-dimethylformamide under light protection and nitrogen protection, slowly add the third mixed solution after stirring for 0.5 to 1 hour, and continue stirring at room temperature for 24 to 28 hours to obtain a fourth mixed solution;

[0018] S17. The fourth mixed solution is subjected to high-speed centrifugation at a rotation speed of 10000-12000 rpm for 15-20 min. The separated solid is washed alternately with N,N-dimethylformamide and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 40-50° C. After drying for 12-14 h, modified nano zinc oxide is obtained and ground into powder for later use.

[0019] Furthermore, the mass ratio of the zinc acetate to tetraphenylporphyrin is 1:(0.01-0.1).

[0020] Furthermore, the mass ratio of tetraphenylporphyrin, N,N-dimethylformamide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(2-4):(0.5-1):(0.5-1).

[0021] Furthermore, the preparation method of the modified nano-hydroxyapatite comprises:

[0022] S21. Dissolve calcium dihydrogen phosphate and calcium hydroxide in purified water under stirring, slowly add hexadecyltrimethylammonium bromide after stirring for 0.5 to 1 h, and adjust the pH value to 10.5 to 11 with an ammonia solution, and continue stirring for 1 to 2 h to obtain a fifth mixed solution;

[0023] S22. The fifth mixed solution is transferred to a hydrothermal reactor for hydrothermal reaction at a temperature of 180 to 200 ° C. and reacted for 12 to 15 hours to obtain a sixth mixed solution;

[0024] S23. The sixth mixed solution is subjected to high-speed centrifugation at a speed of 10000 to 12000 rpm for 10 to 15 min, and the separated solid is washed three times with purified water and anhydrous ethanol alternately and then freeze-dried at a drying temperature of -40 to -60 ° C. After drying for 20 to 24 h, rod-shaped nano-hydroxyapatite is obtained and ground into powder for standby use;

[0025] S24. Dissolve sodium fluoride in purified water under stirring to obtain a sodium fluoride solution, disperse rod-shaped nanohydroxyapatite and γ-methacryloxypropyltrimethoxysilane in purified water and perform ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz. After ultrasonic treatment at room temperature for 0.5 to 1 h, slowly add the sodium fluoride solution, control the drop rate to 1 to 2 mL / min, and continue stirring at room temperature for 4 to 6 h to obtain a seventh mixed solution;

[0026] S25. The seventh mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 15 to 20 minutes. The separated solid is washed 5 times with purified water and then freeze-dried at a drying temperature of -40 to -60°C. After drying for 20 to 24 hours, the modified nano-hydroxyapatite is obtained and ground into powder for later use.

[0027] Furthermore, the modified nano-hydroxyapatite is obtained by surface modification of sodium fluoride and has a rod-like shape, a particle length of 60 to 80 nm, a diameter of 15 to 25 nm, and a specific surface area of ​​180 to 250 m 2 / g.

[0028] Furthermore, the mass ratio of the monocalcium phosphate, calcium hydroxide and sodium fluoride is (1-1.5):(1.5-2):(0.02-0.1).

[0029] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing a tooth polishing agent with antibacterial efficacy, which is applied to the tooth polishing agent with antibacterial efficacy, and comprises the following steps:

[0030] S31. Purified water was added to the container, followed by sodium carboxymethyl cellulose, glycerol, xanthan gum and propylene glycol, and stirred while heating in a water bath at a temperature of 70 to 85 ° C until fully dissolved to obtain an eighth mixed solution;

[0031] S32. The eighth mixed solution was transferred to a vacuum emulsifier, and then cocamidopropyl betaine was slowly added, and silica, modified nano zinc oxide, modified nano hydroxyapatite, gluconolactone, steviol glycosides and sodium benzoate were slowly added after emulsification for 5 to 10 min, and the stirring speed was 2000 to 4000 rpm, and the emulsification was continued for 25 to 30 min to obtain a ninth mixed solution;

[0032] S33. The ninth mixed solution is subjected to vacuum degassing, and the pressure is set to -0.05 to -0.08 MPa. After degassing for 15 to 20 minutes, a uniform and fine paste is obtained, which is the tooth polishing agent.

[0033] Furthermore, the viscosity of the tooth polishing agent is 20000-30000 mPa·s, and the specific gravity is 1.2-1.5 g / cm3 And the pH value is between 6.8 and 7.2.

[0034] The mechanism of action of the above raw material components is as follows:

[0035] Silica (SiO2) is a mesh structure formed by silicon and oxygen atoms connected in a tetrahedral structure. It is usually a white powder. Synthetic fine silica particles are usually used in tooth polishes. As a mild abrasive, it can effectively remove stains and plaque on the surface of teeth. At the same time, silica has moderate hardness and will not excessively wear the enamel while cleaning teeth. Propylene glycol (CH3CH(OH)CH2OH) is a colorless, odorless, sweet-tasting viscous liquid. In tooth polishes, it is mainly used as a humectant and solvent to prevent the product from drying or hardening during use and storage. It also helps to dissolve and disperse other ingredients and improve the touch and spreadability of the product. Glycerin (C3H8O3) is a polyhydroxy alcohol with extremely strong hygroscopicity. It can absorb and retain water. Its good lubricity and solubility can dissolve a variety of organic and inorganic substances. As a humectant and lubricant in tooth polishes, it can prevent the product from drying, maintain appropriate wetness, increase the smoothness of the product, and improve the taste and user experience.

[0036] Sodium Carboxymethyl Cellulose ((C6H7O2(OH)2CH2COONa) n ) is a linear polymer obtained by carboxymethylation and sodiumization of cellulose. It is a white to light yellow odorless and tasteless powder that is easily soluble in water. It is mainly used as a thickener and stabilizer in tooth polishes to increase the viscosity of the product, prevent the separation or precipitation of various components, and form a uniform gel structure, making the tooth polish easy to apply and use. 35 H 49 O 29 ) n ) is a high molecular weight polysaccharide composed of glucose, mannose and glucuronic acid. The main chain is composed of β-1,4-linked D-glucose, and a trisaccharide side chain is connected to every two glucose units. It is a beige or light yellow powder and is easily soluble in water. In tooth polishing agents, it works synergistically with sodium carboxymethyl cellulose to further improve the consistency and stability of the product, provide good suspension, prevent solid particles (such as abrasives) from settling, and enhance the adhesion of the product, so that it can better stay on the toothbrush and tooth surface.

[0037] Cocamidopropyl Betaine (C 19 H 38N2O3) is a zwitterionic surfactant generated by the reaction of coconut oil fatty acids, 3-dimethylaminopropylamine and chloroacetic acid. It is a light yellow viscous liquid or paste, easily soluble in water. It is used as the main cleaning agent and foaming agent in tooth polishes to gently remove dirt and plaque on the tooth surface and produce moderate foam to enhance the cleaning feeling and usage experience. At the same time, the molecular structure of cocamidopropyl betaine contains a hydrophobic fatty acid chain from coconut oil and a hydrophilic betaine group, which enables cocamidopropyl betaine to maintain good surface activity under different pH conditions and has little irritation to the oral mucosa. Stevioside (C 38 H 60 O 18 ) is a natural sweetener extracted from the leaves of the South American stevia plant. In tooth polishes, it can improve the taste of the product and mask the unpleasant taste brought by other ingredients. This diterpene glycoside compound does not contain calories and is not digested and absorbed by the human body, so it will not cause tooth decay and is suitable for long-term use. Sodium benzoate (C7H5NaO2) is a white powder or granule that is easily soluble in water. It is mainly used as a preservative to reduce the pH value in microbial cells, interfere with the metabolic process of microorganisms, inhibit the growth of bacteria, yeast and mold, and extend the shelf life of the product.

[0038] Nano zinc oxide (ZnO) is an inorganic compound with broad-spectrum antibacterial activity. Modified nano zinc oxide is obtained by coupling tetraphenylporphyrin on the surface of nano zinc oxide. Tetraphenylporphyrin is composed of four pyrrole rings connected by a methine bridge to form a macrocyclic ring, and the chemical structure of four phenyl groups connected on the periphery is an important macrocyclic conjugated compound. Tetraphenylporphyrin, as a common photosensitizer, can absorb visible light and produce more active oxygen species, thereby enhancing the antibacterial efficiency of modified nano zinc oxide under natural light. Nano hydroxyapatite (Ca 10 The structure and composition of (PO4)6(OH)2) are similar to those of natural tooth enamel, and it has high biocompatibility. It can penetrate into tiny defects in tooth enamel, promote tooth enamel remineralization, and repair tooth damage. Modified nanohydroxyapatite is prepared by modifying the surface of rod-shaped nanohydroxyapatite with sodium fluoride, which can further increase its binding ability and permeability with tooth enamel, while enhancing its acid resistance and remineralization ability. 10 O6) is a cyclic lactone form of glucose. In aqueous solution, gluconolactone slowly hydrolyzes to gluconic acid, thereby gently lowering the pH value of the solution. This slow acidification process makes it an ideal pH regulator that can adjust the local environment without irritating the oral cavity.

[0039] In the tooth polish with antibacterial effect, modified nano zinc oxide, modified nano hydroxyapatite and gluconolactone play a synergistic role. In the preparation process of tooth polish, modified nano hydroxyapatite prepared by hydrothermal synthesis can be used as a carrier to adsorb chemical substances such as modified nano zinc oxide, silica and sodium carboxymethyl cellulose to form rod-shaped nano microcapsules due to its high specific surface area and rich pore structure. When the tooth polish is applied to the oral environment, gluconolactone slowly hydrolyzes to form gluconic acid, and the carboxyl group (-COOH) on its surface creates a slightly acidic microenvironment, prompting the rod-shaped nano-microcapsules to slowly release chemical substances such as modified nano-zinc oxide, silica and sodium carboxymethyl cellulose. The modified nano-zinc oxide directly releases zinc ions, and the tetraphenylporphyrin coupled to its surface further enhances its binding with the bacterial cell membrane. The two kill bacteria by directly contacting and destroying the function of the bacterial cell membrane. At the same time, tetraphenylporphyrin absorbs visible light, causing the modified nano-zinc oxide to produce electron-hole pairs under light, thereby generating superoxide anions and hydroxyl radicals, providing a sustained and efficient antibacterial effect for the oral environment. Modified nano zinc oxide and modified nano hydroxyapatite complement each other, and through the nano size effect, they further form a denser and more uniform protective layer on the tooth surface, effectively blocking bacteria from contacting the tooth surface. Modified nano zinc oxide provides antibacterial protection and reduces the acidic substances produced by harmful bacteria, while modified nano hydroxyapatite promotes the remineralization of tooth enamel, fills tiny defects on the tooth surface, enhances tooth strength, and releases calcium, phosphorus, and fluoride ions to further improve the oral environment. At the same time, the presence of gluconolactone avoids the agglomeration of modified nano zinc oxide and modified nano hydroxyapatite, improves the dispersibility and stability of the two, and the rod-shaped nano The microcapsules enable the modified nano zinc oxide to continue to exert its effect through sustained release, which not only enhances the antibacterial activity of the modified nano zinc oxide, but also optimizes the remineralization process of the modified nano hydroxyapatite, and further accelerates the hydrolysis of gluconolactone. The three components interact with each other to form a dynamic equilibrium system, which continuously exerts antibacterial and remineralization effects. The antibacterial effect of the modified nano zinc oxide reduces harmful bacteria, and the remineralization effect of the modified nano hydroxyapatite repairs teeth, strengthens tooth structure, and enhances tooth strength. Gluconolactone maintains the oral environment by adjusting the pH value, effectively prevents oral diseases, and provides comprehensive and long-term protection for oral health.

[0040] (3) Beneficial effects

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. Modified nano zinc oxide, modified nano hydroxyapatite and gluconolactone play a role through synergistic effect. Modified nano hydroxyapatite acts as a carrier to adsorb chemical substances such as modified nano zinc oxide, silicon dioxide and sodium carboxymethyl cellulose to form rod-shaped nano microcapsules;

[0043] 2. Gluconolactone promotes the sustained release of rod-shaped nano-microcapsules. Modified nano-zinc oxide kills bacteria by directly releasing zinc ions and directly contacting with tetraphenylporphyrin coupled to its surface. Tetraphenylporphyrin absorbs visible light to generate electron-hole pairs, superoxide anions and hydroxyl radicals, further providing a continuous and efficient antibacterial effect for the oral environment.

[0044] 3. Modified nano zinc oxide and modified nano hydroxyapatite form a dense and uniform protective layer on the tooth surface through the nano size effect, effectively blocking bacteria from contacting the tooth surface. Modified nano zinc oxide provides antibacterial protection, while modified nano hydroxyapatite promotes the remineralization of tooth enamel, releases calcium, phosphorus and fluoride ions, and further improves the oral environment.

[0045] 4. Gluconolactone avoids the agglomeration of modified nano-zinc oxide and modified nano-hydroxyapatite, improves the dispersibility and stability of both, forms a dynamic equilibrium system, continuously exerts antibacterial and remineralization effects, and regulates the pH value to maintain the oral environment, providing comprehensive and long-term protection for oral health. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a SEM image of the modified nano-hydroxyapatite in Example 1 of the present invention;

[0047] Figure 2 This is the SEM image of the modified nano zinc oxide in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The experimental equipment and preparations of the embodiments described below are as follows: electronic balance (Sartorius, Germany), electric constant temperature water bath (Jiangsu Kedao), magnetic stirrer (Shanghai Meiyingpu), ultrasonic instrument (Shanghai Yixin), high-speed centrifuge (Guangzhou Jidi), vacuum homogenizer (Shanghai Noze), vacuum drying oven (Shanghai Jiecheng), rotary evaporator (Shanghai Yaote), hydrothermal reactor (Shanghai Baikal), scanning electron microscope (German Zeiss), specific surface area analyzer (Beijing Best Instrument Technology), freeze dryer (Shanghai Pudong Freeze Drying), pH meter (Shanghai Yidian), constant temperature incubator (Shanghai Hetian); chemicals and reagents were purchased from Sigma-Aldrich.

[0050] Embodiment 1: This embodiment discloses a tooth polishing agent with antibacterial effect, comprising the following raw materials in parts by weight: 10 parts of silicon dioxide, 3 parts of sodium carboxymethyl cellulose, 1.5 parts of xanthan gum, 1.5 parts of propylene glycol, 3 parts of cocamidopropyl betaine, 5 parts of glycerol, 0.8 parts of modified nano-hydroxyapatite, 1.5 parts of gluconolactone, 1.5 parts of stevioside, and 3 parts of sodium benzoate. The tooth polishing agent with antibacterial effect also includes modified nano-zinc oxide, wherein the weight ratio of the modified nano-zinc oxide to silicon dioxide is 1:10, and the modified nano-zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano-zinc oxide is 40-60 nm, and the specific surface area is 120-150 m 2 / g.

[0051] In the antibacterial tooth polish, modified nano zinc oxide, modified nano hydroxyapatite and gluconolactone play a synergistic role. Figure 1 The rod-like structure of modified nano-hydroxyapatite is clearly visible. In the preparation process of tooth polishing agent, the modified nano-hydroxyapatite prepared by hydrothermal synthesis can be used as a carrier to adsorb modified nano-zinc oxide, silicon dioxide, sodium carboxymethyl cellulose and other chemicals to form rod-like nano-microcapsules due to its high specific surface area and rich pore structure. When the tooth polishing agent is used in the oral environment, gluconolactone is slowly hydrolyzed to form gluconic acid (C6H 12 O7), the carboxyl groups (-COOH) on its surface release H + , thus creating a slightly acidic microenvironment. The acidic environment causes the rod-shaped nano-microcapsules to slowly release modified nano-zinc oxide, silicon dioxide, sodium carboxymethyl cellulose and other chemicals. Modified nano-zinc oxide directly releases zinc ions (Zn 2+ ), and the tetraphenylporphyrin coupled to its surface is a macrocyclic compound. Its hydrophobic aromatic ring structure makes it easy to interact with the phospholipid bilayer membrane of bacteria, which further enhances the binding effect with the bacterial cell membrane. The two directly contact and kill bacteria by destroying the function of bacterial cell membrane and interfering with the physiological function of bacteria. At the same time, tetraphenylporphyrin absorbs visible light and excites the modified nano zinc oxide to produce electron-hole pairs under light, thereby generating superoxide anions (O2 - ) and hydroxyl radicals (·OH) and other reactive oxygen species, causing oxidative stress in bacteria, causing oxidative damage to bacterial DNA, proteins and lipids, and ultimately leading to bacterial death. The presence of modified nano zinc oxide ensures that zinc ions (Zn 2+ ), while the photocatalytic reaction ensures the long-term generation of reactive oxygen species, which provides a continuous and efficient antibacterial effect for the oral environment. Figure 2The SEM image of modified nano zinc oxide shows that the particle size of modified nano zinc oxide is uniform and the morphology is spherical. The modified nano zinc oxide and modified nano hydroxyapatite complement each other and further form a denser and more uniform protective layer on the tooth surface through the nano size effect, effectively blocking bacteria from contacting the tooth surface. The modified nano zinc oxide provides antibacterial protection and reduces the acidic substances produced by harmful bacteria, while the modified nano hydroxyapatite releases calcium ions (Ca 2 +), phosphate ion (PO4 3- ) and fluoride ion (F - ) promotes the remineralization of tooth enamel, fills the tiny defects on the tooth surface, and at the same time enhances the resistance of tooth enamel to acid, enhances tooth strength, and further improves the oral environment. At the same time, the presence of gluconolactone avoids the agglomeration of modified nano zinc oxide and modified nano hydroxyapatite. The long chain structure of gluconic acid molecules produced by hydrolysis will form a three-dimensional barrier on the surface of nanoparticles, preventing the aggregation of nanoparticles through the steric hindrance effect. At the same time, the adsorbed gluconic acid molecules also increase the negative charge on the surface of nanoparticles, causing electrostatic repulsion between nanoparticles, thereby improving the dispersibility and stability of the two, ensuring the structural integrity of modified nano zinc oxide and modified nano hydroxyapatite, and the rod-shaped nano microcapsules make the modified nano zinc oxide and modified nano hydroxyapatite have a good effect of slow release. The modified nano zinc oxide can play a continuous role, which not only enhances the antibacterial activity of the modified nano zinc oxide, but also further optimizes the remineralization process of the modified nano hydroxyapatite due to the reduction of bacteria, and further accelerates the hydrolysis of gluconolactone. The gluconic acid molecules produced by hydrolysis continuously adjust the pH value of the local oral environment. The three components influence each other to form a dynamic equilibrium system, which continuously exerts antibacterial and remineralization effects. The antibacterial effect of the modified nano zinc oxide reduces harmful bacteria, and the remineralization effect of the modified nano hydroxyapatite repairs teeth, strengthens tooth structure, and enhances tooth strength. Gluconolactone maintains the oral environment by adjusting the pH value, effectively prevents oral diseases, and provides comprehensive and long-term protection for oral health.

[0052] The preparation method of the modified nano zinc oxide comprises:

[0053] S11. Dissolve zinc acetate in purified water under stirring, stir for 0.5 to 1 h, then slowly add 0.1 mol / L sodium hydroxide solution, raise the temperature to 55 to 65 ° C, continue stirring and react for 4 to 6 h to obtain a first mixed solution;

[0054] S12. The first mixed solution was subjected to high-speed centrifugation at a speed of 6000 to 8000 rpm for 10 to 15 min, and the separated solid was washed three times with purified water and then vacuum dried at a drying temperature of 50 to 60 ° C. After drying for 12 to 14 h, zinc oxide was obtained and ground into powder for standby use;

[0055] S13. Dispersing zinc oxide in anhydrous ethanol under nitrogen protection and subjecting to ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz, subjecting the zinc oxide to ultrasonic treatment at room temperature for 0.5 to 1 h, slowly adding 3-aminopropyltriethoxysilane and subjecting the mixture to reflux at a reflux temperature of 75 to 80 ° C., and subjecting the mixture to reflux for 6 to 8 h to obtain a second mixed solution;

[0056] S14. The second mixed solution was subjected to high-speed centrifugation at a speed of 8000 to 10000 rpm for 15 to 20 min. The separated solid was washed three times with anhydrous ethanol and then vacuum dried at a drying temperature of 45 to 55 ° C. After drying for 8 to 12 h, the nano zinc oxide intermediate was ground into a powder for standby use;

[0057] S15. Dissolve tetraphenylporphyrin in N,N-dimethylformamide under stirring, slowly add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide after stirring for 1 to 2 hours, raise the temperature to 45 to 60° C., continue stirring for 4 to 6 hours to obtain a third mixed solution;

[0058] S16. Disperse the nano zinc oxide intermediate in N,N-dimethylformamide under light protection and nitrogen protection, slowly add the third mixed solution after stirring for 0.5 to 1 hour, and continue stirring at room temperature for 24 to 28 hours to obtain a fourth mixed solution;

[0059] S17. The fourth mixed solution is subjected to high-speed centrifugation at a rotation speed of 10000-12000 rpm for 15-20 min. The separated solid is washed alternately with N,N-dimethylformamide and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 40-50° C. After drying for 12-14 h, modified nano zinc oxide is obtained and ground into powder for later use.

[0060] The mass ratio of the zinc acetate to tetraphenylporphyrin is 1:(0.01-0.1).

[0061] The mass ratio of tetraphenylporphyrin, N,N-dimethylformamide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(2-4):(0.5-1):(0.5-1).

[0062] The preparation method of the modified nano-hydroxyapatite comprises:

[0063] S21. Dissolve calcium dihydrogen phosphate and calcium hydroxide in purified water under stirring, slowly add hexadecyltrimethylammonium bromide after stirring for 0.5 to 1 h, and adjust the pH value to 10.5 to 11 with an ammonia solution, and continue stirring for 1 to 2 h to obtain a fifth mixed solution;

[0064] S22. The fifth mixed solution is transferred to a hydrothermal reactor for hydrothermal reaction at a temperature of 180 to 200 ° C. and reacted for 12 to 15 hours to obtain a sixth mixed solution;

[0065] S23. The sixth mixed solution is subjected to high-speed centrifugation at a speed of 10000 to 12000 rpm for 10 to 15 min, and the separated solid is washed three times with purified water and anhydrous ethanol alternately and then freeze-dried at a drying temperature of -40 to -60 ° C. After drying for 20 to 24 h, rod-shaped nano-hydroxyapatite is obtained and ground into powder for standby use;

[0066] S24. Dissolve sodium fluoride in purified water under stirring to obtain a sodium fluoride solution, disperse rod-shaped nanohydroxyapatite and γ-methacryloxypropyltrimethoxysilane in purified water and perform ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz. After ultrasonic treatment at room temperature for 0.5 to 1 h, slowly add the sodium fluoride solution, control the drop rate to 1 to 2 mL / min, and continue stirring at room temperature for 4 to 6 h to obtain a seventh mixed solution;

[0067] S25. The seventh mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 15 to 20 minutes. The separated solid is washed 5 times with purified water and then freeze-dried at a drying temperature of -40 to -60°C. After drying for 20 to 24 hours, the modified nano-hydroxyapatite is obtained and ground into powder for later use.

[0068] The modified nano-hydroxyapatite is obtained by surface modification of sodium fluoride and is rod-shaped with a particle length of 60 to 80 nm, a diameter of 15 to 25 nm, and a specific surface area of ​​180 to 250 m 2 / g.

[0069] The mass ratio of the monocalcium phosphate, calcium hydroxide and sodium fluoride is (1-1.5):(1.5-2):(0.02-0.1).

[0070] A method for preparing a tooth polishing agent with antibacterial effect, which is applied to the tooth polishing agent with antibacterial effect, comprises the following steps:

[0071] S31. Purified water was added to the container, followed by sodium carboxymethyl cellulose, glycerol, xanthan gum and propylene glycol, and stirred while heating in a water bath at a temperature of 70 to 85 ° C until fully dissolved to obtain an eighth mixed solution;

[0072] S32. The eighth mixed solution was transferred to a vacuum emulsifier, and then cocamidopropyl betaine was slowly added, and silica, modified nano zinc oxide, modified nano hydroxyapatite, gluconolactone, steviol glycosides and sodium benzoate were slowly added after emulsification for 5 to 10 min, and the stirring speed was 2000 to 4000 rpm, and the emulsification was continued for 25 to 30 min to obtain a ninth mixed solution;

[0073] S33. The ninth mixed solution is subjected to vacuum degassing, and the pressure is set to -0.05 to -0.08 MPa. After degassing for 15 to 20 minutes, a uniform and fine paste is obtained, which is the tooth polishing agent.

[0074] The tooth polishing agent has a viscosity of 20,000 to 30,000 mPa·s and a specific gravity of 1.2 to 1.5 g / cm 3 And the pH value is between 6.8 and 7.2.

[0075] Example 2: This example discloses a tooth polishing agent with antibacterial effect, comprising the following raw materials in parts by weight: 12 parts of silicon dioxide, 4 parts of sodium carboxymethyl cellulose, 2 parts of xanthan gum, 2 parts of propylene glycol, 4 parts of cocamidopropyl betaine, 6 parts of glycerol, 1 part of modified nano-hydroxyapatite, 2 parts of gluconolactone, 2 parts of stevioside, and 4 parts of sodium benzoate. The tooth polishing agent with antibacterial effect also includes modified nano-zinc oxide, wherein the weight ratio of the modified nano-zinc oxide to silicon dioxide is 1:12, and the modified nano-zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano-zinc oxide is 40-60 nm, and the specific surface area is 120-150 m 2 / g. The preparation method of the modified nano zinc oxide and modified nano hydroxyapatite in this embodiment is consistent with that in Example 1. The preparation method of a tooth polishing agent with antibacterial effect in this embodiment is consistent with that in Example 1.

[0076] Example 3: This example discloses a tooth polishing agent with antibacterial effect, comprising the following raw materials in parts by weight: 8 parts of silicon dioxide, 2 parts of sodium carboxymethyl cellulose, 1 part of xanthan gum, 1 part of propylene glycol, 2 parts of cocamidopropyl betaine, 4 parts of glycerol, 0.5 parts of modified nano-hydroxyapatite, 1 part of gluconolactone, 1 part of stevioside, and 2 parts of sodium benzoate. The tooth polishing agent with antibacterial effect also includes modified nano-zinc oxide, wherein the weight ratio of the modified nano-zinc oxide to silicon dioxide is 1:8, and the modified nano-zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano-zinc oxide is 40-60 nm, and the specific surface area is 120-150 m 2 / g. The preparation method of the modified nano zinc oxide and modified nano hydroxyapatite in this embodiment is consistent with that in Example 1. The preparation method of a tooth polishing agent with antibacterial effect in this embodiment is consistent with that in Example 1.

[0077] Control group 1: The difference between this embodiment and embodiment 1 is that modified nano zinc oxide is not contained. This embodiment discloses a tooth polishing agent with antibacterial effect, comprising the following raw materials in parts by weight: 10 parts of silicon dioxide, 3 parts of sodium carboxymethyl cellulose, 1.5 parts of xanthan gum, 1.5 parts of propylene glycol, 3 parts of cocamidopropyl betaine, 5 parts of glycerol, 0.8 parts of modified nano hydroxyapatite, 1.5 parts of gluconolactone, 1.5 parts of steviol glycosides, and 3 parts of sodium benzoate. The preparation method of the modified nano hydroxyapatite in this embodiment is consistent with that in embodiment 1. The preparation method of a tooth polishing agent with antibacterial effect in this embodiment is consistent with that in embodiment 1.

[0078] Control group 2: The difference between this embodiment and embodiment 1 is that modified nano-hydroxyapatite is not contained. This embodiment discloses a tooth polishing agent with antibacterial effect, comprising the following raw materials in parts by weight: 10 parts of silicon dioxide, 3 parts of sodium carboxymethyl cellulose, 1.5 parts of xanthan gum, 1.5 parts of propylene glycol, 3 parts of cocamidopropyl betaine, 5 parts of glycerol, 1.5 parts of gluconolactone, 1.5 parts of stevioside, and 3 parts of sodium benzoate. The tooth polishing agent with antibacterial effect also includes modified nano zinc oxide, and the modified nano zinc oxide and silicon dioxide are in a weight ratio of 1:10. The modified nano zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano zinc oxide is 40-60nm, and the specific surface area is 120-150m 2 / g. The preparation method of the modified nano zinc oxide in this embodiment is consistent with that in Example 1. The preparation method of a tooth polishing agent with antibacterial effect in this embodiment is consistent with that in Example 1.

[0079] Control group 3: The difference between this embodiment and embodiment 1 is that it does not contain gluconolactone. It includes the following raw materials by weight: 10 parts of silicon dioxide, 3 parts of sodium carboxymethyl cellulose, 1.5 parts of xanthan gum, 1.5 parts of propylene glycol, 3 parts of cocamidopropyl betaine, 5 parts of glycerol, 0.8 parts of modified nano-hydroxyapatite, 1.5 parts of stevioside, and 3 parts of sodium benzoate. The tooth polishing agent with antibacterial effect also includes modified nano-zinc oxide, and the modified nano-zinc oxide and silicon dioxide are in a weight ratio of 1:10. The modified nano-zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano-zinc oxide is 40-60nm, and the specific surface area is 120-150m 2 / g. The preparation method of the modified nano zinc oxide and modified nano hydroxyapatite in this embodiment is consistent with that in Example 1. The preparation method of a tooth polishing agent with antibacterial effect in this embodiment is consistent with that in Example 1.

[0080] Effect evaluation: In vitro antibacterial experiment: Five common oral bacterial strains were selected, namely Streptococcus mutans, Porphyromonas gingivalis, Candida burnetii, Lactococcus lactis and Enterococcus faecalis. All strains were purchased from the China Microbiological Culture Collection Center. The specific experimental method is as follows: (1) Preparation of bacterial suspension: Inoculate the strain on a slant nutrient medium, culture at 37°C for 6 to 8 hours, and then resuspend the bacteria with sterile saline to adjust the concentration to 1.5×10 8 CFU / mL, set aside; (2) Inoculation of bacteria: Dip a sterile cotton swab into the bacterial suspension with adjusted turbidity, and evenly apply it on the agar surface three times, rotating the plate 60° each time to ensure that the bacteria are evenly distributed, and let it stand for 5 minutes to allow the bacterial suspension to be absorbed by the agar; (3) Tooth polishing agent sample test: Take a sterile dry filter paper, punch a 6mm hole with a hole puncher, and put it into the tooth polish prepared by each experimental group to ensure that it is fully soaked. Similarly, soak another sterile dry filter paper in sterile saline as a blank control, and place the filter paper soaked with tooth polish on the plate. Gently press the filter paper in the center of the agar plate inoculated with bacteria to ensure full contact with the agar surface; (4) Cultivation: Place the plate upside down in a 37°C incubator. Aerobic bacteria such as Streptococcus mutans, Candida burnetii, Lactococcus lactis and Enterococcus faecalis should be cultured in an aerobic incubator for 24 to 48 hours, and anaerobic bacteria such as Porphyromonas gingivalis should be cultured in an anaerobic incubator for 48 to 72 hours; (5) Measuring the inhibition zone: After the incubation period, remove the plate and measure the diameter of the inhibition zone with a vernier caliper or ruler to an accuracy of 0.1 mm. Measure each plate three times and take the average value.

[0081] Table 1 Statistics of antibacterial zone size of tooth polish (mm)

[0082] Group Streptococcus mutans Porphyromonas gingivalis Candida burnetii Lactococcus lactis Enterococcus faecalis Example 1 15.8 14.2 1 5.7 16.2 1 5.4 Example 2 15.2 14.0 1 5.5 16.2 1 5.2 Example 3 14.5 14.0 15.0 15.5 14.4 Control group 1 11.4 10.2 12.4 11.6 12.2 Control group 2 13.6 12.9 1 3.8 1 3.5 13.9 Control group 3 8.9 10.4 11.2 10.6 9.8 Blank Group 4.3 2.1 5.6 4.4 3.7

[0083] Table 1 is the statistical results of the antibacterial zone size determination of the tooth polishes in each experimental group. It can be seen from Table 1 that there are obvious differences in the antibacterial effects of the tooth polishes prepared in each experimental group. The blank group shows no antibacterial effect. By comparing the antibacterial effects of the tooth polishes prepared in Examples 1 to 3 with those in Control Groups 1 to 3, it can be found that, on the whole, the antibacterial effects of the tooth polishes prepared in Examples 1 to 3 are better, and the diameter of the antibacterial zone is between 14 and 17 mm, showing a strong antibacterial effect, and the diameter of the antibacterial zone of the tooth polish prepared in Example 1 is larger than that of Example 2 and Example 3, which shows that the antibacterial effect of the tooth polish prepared in Example 1 is the best, while the diameter of the antibacterial zone of the tooth polishes prepared in Control Groups 1 to 3 is ≤14 mm, showing a weak antibacterial effect, which shows that by adding the three substances of modified nano zinc oxide, modified nano hydroxyapatite and gluconolactone at the same time in the preparation process of the tooth polish, a tooth polish with excellent antibacterial effect can be obtained.

[0084] Through the above limited experiments, the application effect of the tooth polishing agent with antibacterial effect of Example 1 of the present invention is significant. By adding modified nano zinc oxide, gluconolactone and modified nano hydroxyapatite at the same time during the production process, the antibacterial effect of the tooth polishing agent can be significantly improved, and a more lasting and effective antibacterial environment can be provided for the oral cavity. The three form a dynamic balance system, which not only ensures the polishing effect, but also further strengthens the tooth structure by repairing tiny defects in the enamel, enhances tooth strength, and regulates the pH value to maintain the oral environment, effectively prevents oral diseases, and provides comprehensive and long-term protection for oral health.

[0085] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A tooth polishing agent with antibacterial effect, characterized in that: The invention comprises the following raw materials in parts by weight: 8 to 12 parts of silicon dioxide, 2 to 4 parts of sodium carboxymethyl cellulose, 1 to 2 parts of xanthan gum, 1 to 2 parts of propylene glycol, 2 to 4 parts of cocamidopropyl betaine, 4 to 6 parts of glycerol, 0.5 to 1 part of modified nano-hydroxyapatite, 1 to 2 parts of gluconolactone, 1 to 2 parts of steviol glycoside, and 2 to 4 parts of sodium benzoate; The tooth polishing agent with antibacterial effect also includes: Modified nano zinc oxide; The modified nano zinc oxide and silicon dioxide are in a weight ratio of 1:(8-12); The modified nano zinc oxide is obtained by surface coupling tetraphenylporphyrin, and the particle size of the modified nano zinc oxide is 40-60nm, and the specific surface area is 120-150m 2 / g.

2. A tooth polishing agent with antibacterial effect according to claim 1, characterized in that: The preparation method of the modified nano zinc oxide comprises: S11. Dissolve zinc acetate in purified water under stirring, stir for 0.5 to 1 h, then slowly add 0.1 mol / L sodium hydroxide solution, raise the temperature to 55 to 65 ° C, continue stirring and react for 4 to 6 h to obtain a first mixed solution; S12. The first mixed solution was subjected to high-speed centrifugation at a speed of 6000 to 8000 rpm for 10 to 15 min, and the separated solid was washed three times with purified water and then vacuum dried at a drying temperature of 50 to 60 ° C. After drying for 12 to 14 h, zinc oxide was obtained and ground into powder for standby use; S13. Dispersing zinc oxide in anhydrous ethanol under nitrogen protection and subjecting to ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz, subjecting the zinc oxide to ultrasonic treatment at room temperature for 0.5 to 1 h, slowly adding 3-aminopropyltriethoxysilane and subjecting the mixture to reflux at a reflux temperature of 75 to 80 ° C., and subjecting the mixture to reflux for 6 to 8 h to obtain a second mixed solution; S14. The second mixed solution was subjected to high-speed centrifugation at a speed of 8000 to 10000 rpm for 15 to 20 min. The separated solid was washed three times with anhydrous ethanol and then vacuum dried at a drying temperature of 45 to 55 ° C. After drying for 8 to 12 h, the nano zinc oxide intermediate was ground into a powder for standby use; S15. Dissolve tetraphenylporphyrin in N,N-dimethylformamide under stirring, slowly add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide after stirring for 1 to 2 hours, raise the temperature to 45 to 60° C., continue stirring for 4 to 6 hours to obtain a third mixed solution; S16. Disperse the nano zinc oxide intermediate in N,N-dimethylformamide under light protection and nitrogen protection, slowly add the third mixed solution after stirring for 0.5 to 1 hour, and continue stirring at room temperature for 24 to 28 hours to obtain a fourth mixed solution; S17. The fourth mixed solution is subjected to high-speed centrifugation at a rotation speed of 10000-12000 rpm for 15-20 min. The separated solid is washed alternately with N,N-dimethylformamide and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 40-50° C. After drying for 12-14 h, modified nano zinc oxide is obtained and ground into powder for later use.

3. A tooth polishing agent with antibacterial effect according to claim 2, characterized in that: The mass ratio of the zinc acetate to tetraphenylporphyrin is 1:(0.01-0.1).

4. A tooth polishing agent with antibacterial effect according to claim 2, characterized in that: The mass ratio of tetraphenylporphyrin, N,N-dimethylformamide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(2-4):(0.5-1):(0.5-1).

5. The tooth polishing agent with antibacterial effect according to claim 1, characterized in that: The preparation method of the modified nano-hydroxyapatite comprises: S21. Dissolve calcium dihydrogen phosphate and calcium hydroxide in purified water under stirring, slowly add hexadecyltrimethylammonium bromide after stirring for 0.5 to 1 h, and adjust the pH value to 10.5 to 11 with an ammonia solution, and continue stirring for 1 to 2 h to obtain a fifth mixed solution; S22. The fifth mixed solution is transferred to a hydrothermal reactor for hydrothermal reaction at a temperature of 180 to 200 ° C. and reacted for 12 to 15 hours to obtain a sixth mixed solution; S23. The sixth mixed solution is subjected to high-speed centrifugation at a speed of 10000 to 12000 rpm for 10 to 15 min, and the separated solid is washed three times with purified water and anhydrous ethanol alternately and then freeze-dried at a drying temperature of -40 to -60 ° C. After drying for 20 to 24 h, rod-shaped nano-hydroxyapatite is obtained and ground into powder for standby use; S24. Dissolve sodium fluoride in purified water under stirring to obtain a sodium fluoride solution, disperse rod-shaped nanohydroxyapatite and γ-methacryloxypropyltrimethoxysilane in purified water and perform ultrasonic treatment at an ultrasonic frequency of 40 to 50 kHz. After ultrasonic treatment at room temperature for 0.5 to 1 h, slowly add the sodium fluoride solution, control the drop rate to 1 to 2 mL / min, and continue stirring at room temperature for 4 to 6 h to obtain a seventh mixed solution; S25. The seventh mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 15 to 20 minutes. The separated solid is washed 5 times with purified water and then freeze-dried at a drying temperature of -40 to -60°C. After drying for 20 to 24 hours, the modified nano-hydroxyapatite is obtained and ground into powder for later use.

6. A tooth polishing agent with antibacterial effect according to claim 5, characterized in that: The modified nano-hydroxyapatite is obtained by surface modification of sodium fluoride and is rod-shaped with a particle length of 60 to 80 nm, a diameter of 15 to 25 nm, and a specific surface area of ​​180 to 250 m 2 / g.

7. The tooth polishing agent with antibacterial effect according to claim 5, characterized in that: The mass ratio of the monocalcium phosphate, calcium hydroxide and sodium fluoride is (1-1.5):(1.5-2):(0.02-0.1).

8. A method for preparing a tooth polishing agent with antibacterial effect, which is used for preparing a tooth polishing agent with antibacterial effect as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: S31. Purified water was added to the container, followed by sodium carboxymethyl cellulose, glycerol, xanthan gum and propylene glycol, and stirred while heating in a water bath at a temperature of 70 to 85 ° C until fully dissolved to obtain an eighth mixed solution; S32. The eighth mixed solution was transferred to a vacuum emulsifier, and then cocamidopropyl betaine was slowly added, and silica, modified nano zinc oxide, modified nano hydroxyapatite, gluconolactone, steviol glycosides and sodium benzoate were slowly added after emulsification for 5 to 10 min, and the stirring speed was 2000 to 4000 rpm, and the emulsification was continued for 25 to 30 min to obtain a ninth mixed solution; S33. The ninth mixed solution is subjected to vacuum degassing, and the pressure is set to -0.05 to -0.08 MPa. After degassing for 15 to 20 minutes, a uniform and fine paste is obtained, which is the tooth polishing agent.

9. The method for preparing a tooth polishing agent with antibacterial effect according to claim 8, characterized in that: The tooth polishing agent has a viscosity of 20,000 to 30,000 mPa·s and a specific gravity of 1.2 to 1.5 g / cm 3 And the pH value is between 6.8 and 7.2.

Citation Information

Patent Citations

  • Fluoride-free toothpaste and preparation method thereof

    CN106943335A

  • Preparation method of zinc oxide molecular sieve photocatalyst for sewage treatment

    CN108404968A

  • Water-based single-component antibacterial whiteboard paint for children and preparation method of water-based single-component antibacterial whiteboard paint

    CN115109513A

  • Biodegradable composite material with antibacterial properties

    RU2807592C1

Cited By

  • Wear-resistant low-shrinkage dental resin composite material and preparation method thereof

    CN120227285A